The influence of leadership style and organizational culture on the performance of employees through work discipline in electrical industry - Sirajuddin, Sirajuddin; Arina, Faula; Ferdika, Rezky (Universitas Sultan Ageng Tirtayasa, 2023)
Planned and sustainable human resource development is important for every organization or company. Several factors that influence employee performance include leadership style, organizational culture, and work discipline. This research aims to determine the influence of leadership style and organizational culture on employee performance through work discipline in the electrical industry. The research method used is quantitative research, and quantitative data was collected through a questionnaire survey to analyze the relationship between latent variables. This research involved 133 samples of organic employees from one of the electricity companies in Indonesia. The data analysis technique uses SEM PLS with Smart-PLS. The research results show that the application of leadership style and organizational culture in the electricity industry has a positive and significant effect on work discipline and employee performance. Likewise, work discipline also has a positive and significant effect on employee performance. Furthermore, leadership style and organizational culture have a positive and significant effect on employee performance through work discipline as an intervening variable. So, it can be concluded that the application of leadership style and organizational culture through work discipline has a positive and significant effect on employee performance in the electrical industry.